Impacts of Global Solid Biofuel Stove Emissions on Ambient Air Quality and Human Health - Huang, Yaoxian (Geohealth, 2021)
Global solid biofuel stove emissions strongly impact air quality, climate change, and human health. However, investigations of the impacts of global solid biofuel stove emissions on human health associated with PM(2.5) (particulate matter with aerodynamic diameter ≤2.5 μm) and ozone (O(3)) are limited. Here, we quantify the impacts of global solid biofuel stove emissions on ambient PM(2.5) and O(3) air quality and the associated human health effects for the year 2010, using the Community Atmosphere Model coupled with Chemistry version 5.3. Annual mean surface PM(2.5) concentrations from global solid biofuel stove emissions averaged over 2006–2010 are up to 23.1 μg m(−3), with large impacts found over China, India, sub‐Saharan Africa, and eastern and central Europe. For surface O(3) impacts, we find that global solid biofuel stove emissions lead to increases in surface O(3) concentrations by up to 5.7 ppbv for China, India, and sub‐Saharan Africa, and negligible impacts or reductions of up to 0.5 ppbv for the US, Europe, and parts of South America. Global solid biofuel stove emissions for the year 2010 contribute to 382,000 [95% confidence interval (95CI): 349,000–409,000] annual premature deaths associated with PM(2.5) and O(3) exposure, with the corresponding years of life lost as 8.10 million years (95CI: 7.38–8.70 million years). Our study highlights air quality and human health benefits of mitigating emissions from the global solid biofuel stove sector, especially over populous regions of low‐income and middle‐income countries, through promoting clean household energy programs for the residential energy supply.